Chemodialysis of organic acids using ABPBI-based hollow fiber membranes - Gawas, Saroj; Alladi, Lavanya; Kharul, Ulhas K. (Journal of Membrane Science, 2024)
Organic acids are a class of essential commodity chemicals used in various industries. Their production methods are shifting from conventional chemicals to fermentation, driven by green process strategies, environmental regulations, cost feasibility, etc. Separating formed acid from the fermentation broth is a primary technological barrier. Conventional methods are complex and impose environmental issues. A promising approach, `Chemodialysis,' capable of transforming the techno-economical feasibility of acid recovery scenario by reducing the number of steps, needs further investigation. This work evaluates scalable hollow fiber membranes based on poly(2,5-benzimidazole) (ABPBI) for chemically assisted dialysis, viz., Chemodialysis. Sorption analyses of commercially significant organic acids (acetic, lactic, and glycolic acid) and nonacidic solutes (NaCl and glucose) were performed using conventional flat sheet samples to assess their role in governing permeation characteristics. The transport properties of acids in the presence of NaCl and glucose as co-solutes were analyzed using hollow fiber membranes. The high selectivity of acid over nonacidic solutes ranges from 400-22,400, coupled with high acid permeability, enhances the applicability of Chemodialysis for the separation of acids using hollow fiber membranes. The fluxes of acids (acetic, glycolic, and lactic) through dense, similar to 100 mu m thick, scalable hollow fiber membranes ranging from 10.9 to 13.12 g/m(2)h are highly appreciable.
Keywords: 5-benzimidazole); Acid separation; Chemodialysis; Hollow fiber membranes; Organic acids; Poly(2

Scalable, interfacially synthesized, covalent-organic framework (COF)-based thin-film composite (TFC) hollow fiber membranes for organic solvent nanofiltration (OSN) - Kunjattu, Shebeeb H.; Thorat, Nitin M.; Gawas, Saroj; Kharul, Ulhas K. (ACS Applied Materials and Interfaces, 2024)
Covalent organic frameworks have great potential for energy-efficient molecular sieving-based separation. However, it remains challenging to implement COFs as an alternative membrane material due to the lack of a scalable and cost-effective fabrication mechanism. This work depicts a new method for fabricating a scalable in situ COF hollow fiber (HF) membrane by an interfacial polymerization (IP) approach at room temperature. The 2D COF film was constructed on a polyacrylonitrile HF substrate using aldehyde (1,3,5-trimethylphloroglucinol, Tp) and amine (4,4 `-azodianiline (Azo) and 4,4 `,4 `'-(1,3,5-triazine- 2,4,6-triyl) trianiline (Tta)) as precursors. The COF membrane on the PAN substrate showed 99% rejection of Direct red-80 with remarkable solvent permeance. The rejection analysis revealed that the structural aspects of the solute molecule play a major role in rejection rather than the molecular weight. We further optimized the precursor concentrations to improve the permeation performance of the resulting membrane. The durability study reveals excellent stability of the membrane toward organic solvents. This study also demonstrated the easy scalability of the membrane fabrication approach. The approach was further extrapolated to fabricate a cation-based COF membrane. These charged membranes exhibited an enhanced rejection performance. Finally, this approach can facilitate industrially challenging molecular sieving applications using COF-based membranes.
Keywords: covalent-organic framework; hollow fiber; interfacial polymerization; organic solvent nanofiltration; selective COF membrane